Metaphorical Feelings in Indonesian Poetry of the 20th Century (Based on the Works of Sapardi Djoko Damono, Sanusi Pane, and Chairil Anwar) - Lytvynenko, Tetiana; Ni'am, Ahmad Khoirun (Universitas Muria Kudus, 2023)
Puisi Indonesia abad ke-20 sedang aktif diteliti oleh para ilmuwan. Namun, topik reproduksi perasaan, yang penting untuk pemahaman menyeluruh tentang isi karya periode ini, praktis tidak dipelajari. Tujuan penelitian ini adalah untuk mendeskripsikan metafora perasaan dalam puisi Sapardi Djoko Damono, Sanusi Pane, dan Chairil Anwar, berdasarkan terjemahan Antologi Puisi Indonesia Abad 20. Jenis penelitian yang digunakan dalam penelitian ini adalah kualitatif. Sumber data primer yang digunakan dalam penelitian ini adalah tujuh judul puisi terpilih karya Sapardi Djoko Damono, Sanusi Pane, dan Chairil Anwar. Data tersebut berupa kata, frasa, klausa atau kalimat yang mengandung metafora dari puisi penyair. Hasil penelitian menunjukkan bahwa metafora perasaan dalam karya Sapardi Djoko Damono, Sanusi Pane dan Chairil Anwar menggambarkan perasaan yang berbeda terkait cinta dan persahabatan, kesedihan dan kebahagiaan, lingkungan, hidup dan mati, Tanah Air dan lain-lain.Indonesian poetry of the 20th century is being actively researched by scientists. However, the topic of the reproduction of feelings, which is important for a thorough understanding of the content of the works of this period, is practically not studied. The purpose of this research is to describe the metaphorization of feelings in the poetry of Sapardi Djoko Damono, Sanusi Pane, and Chairil Anwar, based on the translation of the 20th Century Indonesian Poetry Anthology. The type of research used in this research is qualitative. The primary data sources used in this study were seven selected poetry titles by Sapardi Djoko Damono, Sanusi Pane, and Chairil Anwar. The data are in the form of words, phrases, clauses or sentences that contain metaphors from the poets’ poetries. The results of the study show that the metaphors of feelings in the works of Sapardi Djoko Damono, Sanusi Pane and Chairil Anwar describe different feelings related to love and friendship, sadness and happiness, environment, life and death, Motherland and others.